(untitled) (Research, Society and Development, 2024)
The theme of sharks in general society is surrounded by negative stereotypes that label them as villains and killers of the seas. On the other hand, children’s animated films, in addition to constituting an indispensable playful tool for Zoology Teaching, also approach the subject from a new perspective, in order to break with stereotypes and shed light on these myths. Given this, the work aimed to carry out a comparative analysis and describe the representation of sharks as characters in animated films, considering the main biological concepts presented. To this end, three titles from different decades were selected, namely “Finding Nemo” (2003), “Seefood - a fish out of water” (2011) and “Companhia das Seals” (2021). From this study, it was possible to verify that the three films have relevant information with the potential to guide valuable discussions on various topics in Zoology classes, which is, therefore, a fundamental didactic resource to facilitate the teaching-learning process, as well as act in a significant way in demystifying the topic of sharks and consequently in conserving biodiversity. The comparative analysis of the aspects of these characters made it evident that the change of decades caused certain variations in the way sharks are represented in children’s films, mainly as a result of advances in technology.